Aristotelian cosmology and its influence on late medieval astrology - Silva Guevara, Lizardo David (2022)
Aristotelian cosmology and physics received by the medieval occident justify the scientific view of the (medieval) astrology. How so? Well, let’s consider the aristotelic theory of the tripartite man: body, soul and pneuma (as the link between both and as the reason of the ability of the soul to catch inmaterial knowledge from the material one). Now, let’s consider the aristotelian view of the cosmos as a system of celestial spheres –moved by the Unmoved mover – and that influences on earth in a way that they produce its movement. These two prior considerations will serve as a support to talk about the relation man-cosmos throughtout the pneuma (made from the aristotelian quintessence, the eter). This view, altogether, will be useful to justify some medieval views about the astrology as a scientific discipline, as starting in natural philosophy. Once this cosmological system falls, the magic-astrological believes that were supported by so will subsequently lose their epistemic-scientific level.